Microservices Design Patterns In . NET Making Sense of Microservices Design and Architecture Using . NET Core - Williams, Trevoir (Packt Publishing, Limited, 2023)
Learn to be deliberate and intentional in your design, technology, and pattern choices when developing an application using a microservices architecture. Key Features Tackle common design problems when developing a microservices application using .NET Core Explore applying S.O.L.I.D development principles in developing a stable microservice application Use your knowledge to solve common microservice application design challenges Book Description Are you a developer who needs to fully understand the different patterns and benefits that they bring to designing microservices? If yes, then this book is for you. Microservices Design Patterns in .NET will help you appreciate the various microservice design concerns and strategies that can be used to navigate them. Making a microservice-based app is no easy feat and there are many concerns that need to be addressed. As you progress through the chapters of this guide, you'll dive headfirst into the problems that come packed with this architectural approach, and then explore the design patterns that address these problems. You'll also learn how to be deliberate and intentional in your architectural design to overcome major considerations in building microservices. By the end of this book, you'll be able to apply critical thinking and clean coding principles when creating a microservices application using .NET Core. What you will learn Use Domain-Driven Design principles in your microservice design Leverage patterns like event sourcing, database-per-service, and asynchronous communication Build resilient web services and mitigate failures and outages Ensure data consistency in distributed systems Leverage industry standard technology to design a robust distributed application Find out how to secure a microservices-designed application Use containers to handle lightweight microservice application deployment Who this book is for If you are a .NET developer, senior developer, software architect, or DevOps engineer who wants to explore the pros and cons, intricacies, and overall implementation of microservice architecture, then this book is for you. You'll also get plenty of useful insights if you're seeking to expand your knowledge of different design patterns and supporting technologies. Basic experience with application and API development with .NET Core (2+) and C# will help you get the most out of this book.